PARADISE-MI – event rates and treatment effect of sacubitril/valsartan v ramipril by the presence or absence of transient pulmonary congestion and/or LVEF less or greater than 40. (3rd October 2022) - Petrie, M; Solomon, S; Claggett, B L; Jering, K; Steg, G; Granger, C; Lewis, E; Kober, L; Mann, D; Rouleau, J L; McMurray, J J; Maggioni, A; et al.
Abstract: Background/Introduction: Sacubitril/valsartan was compared to ramipril in patients with acute myocardial infarction in the PARADISE-MI trial. In the whole trial population sacubitril/valsartan did not reduce the composite primary outcome of CV death or incident heart failure compared to ramipril. Whether or not event rates and/or treatment effects vary in patients with different baseline characteristics is unknown. Purpose: To investigate a) event rates b) the treatment effect of sacubitril/valsartan compared to ramipril and c) safety by the presence or absence of transient pulmonary congestion and/or left ventricular ejection fraction (LVEF) ≤40%. Methods: PARADISE-MI was a double-blind, randomised clinical trial that compared sacubitril/valsartan to ramipril in 5661 patients with an acute myocardial infarction with either LVEF ≤40% and/or transient pulmonary congestion. 3 groups were investigated: 1) LVEF ≤40% with pulmonary congestion (n=2012) and 2) LVEF ≤40% without pulmonary congestion (n=2596) and 3) LVEF not ≤40% with pulmonary congestion (n=1044). Results: Patients with pulmonary congestion (with and without LVEF ≤40%) were more likely to have had a prior MI, prior CABG or PCI, had more atrial fibrillation and were more often treated with mineralocorticoid receptor antagonists and diuretics than patients with no pulmonary congestion and LVEF ≤40%. Patients with LVEF ≤40% and pulmonary congestion had more than twice the rate of the primary composite outcome compared to those with LVEF ≤40% without pulmonary congestion: 10.2 (95% CI 9.2–11.3) vs. 4.8 (4.3–5.5) events per 100 patient-years, respectively). Patients with pulmonary congestion and LVEF not ≤40% had an intermediate event rate (6.6, 5.5–7.9, events per 100 patient-years). A similar pattern of event rates was seen for the components of the primary outcome and for all secondary outcomes whether Clinical Events Committee or investigator-reported events were analysed. The treatment effect of sacubitril/ valsartan versus ramipril did not vary between the 3 congestion/ LVEF subgroups. The safety of sacubitril/valsartan compared to ramipril did not vary between congestion/LVEF subgroups. Conclusion: Patients with pulmonary congestion with or without LVEF ≤40% had higher rates of primary and all secondary outcomes than those without pulmonary congestion and LVEF ≤40%. The treatment effect, and safety, of sacubitril/valsartan compared to ramipril was consistent in patients with or without pulmonary congestion and with or without LVEF ≤40%. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novartis